Application of the Lurik Pedan Klaten Local Wisdom Booklet using the RWPS Model to Empower Students’ Environmental Literacy - Firdaus, Prisma Satria; Suciati, Suciati; Utami, Budi; Gunawan, Kadek Dwi Hendratma; Bramastia, Bramastia (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to investigate the effectiveness of using the Lurik Pedan Klaten Local Wisdom Booklet with the Real World Problem Solving (RWPS) model to empower environmental literacy in VII students in science learning. This studi user a quasi-experimental method with a pretest-posttest control group design. The sample consisted of VII students at SMP N 1 Kebakkramat, selected using cluster random sampling. The research instrument used was a environmental literacy test with pretest and posttest and environmental literacy questionnaires. Quantitative data analysis used descriptive statistic, prerequisite test, and hypothesis testing using t-test.  The results showed that the Sig. (2-tailed) value was 0.000 < 0.05 with a significance level of 5%. The average knowledge test scores for the experimental class (73.9) and the control class (66.4), the average attitude questionnaire scores for the experimental class (34.4) and the control class (34.4), and the average behavior questionnaire scores for the experimental class (34.16) and the control class (33.9) showed significant differences. It can be concluded that the experimental class that used the Lurik Pedan Klaten local wisdom booklet with the RWPS model significantly influenced students' environmental literacy skills. The implications of these research results indicate that the application of the Lurik Pedan Klaten local wisdom booklet using the RWPS model can be a learning resource in science education to empower students' environmental literacy, so that students can more easily understand concepts through problems that are relevant to their daily lives.